Pengembangan Media Pembelajaran Bahasa Arab Berbasis Android dengan Teori Pembelajaran Interaktif - Latifah; Ma'arif, M. Syamsul; Afyuddin, Moh. Sholeh (Al-Wasil, 2024)
The purpose of this study, (1) Knowing the feasibility of android-based Arabic learning media with interactive learning theory to improve the learning outcomes of class X MA Al Huda Kediri City students. (2)Knowing the effectiveness of Arabic learning media based on Android to improve the learning outcomes of students in class X MA Al Huda Kota Kediri. This type of research and development in this study uses the type of Research and Development (R&D) with the ADDIE model (Analyze, Design, Develop, Implementation, and Evaluate). The instruments in this study are Observation, Interview, Questionnaire Assessment of Media Experts, Material Experts and Construct Experts, Tests, and Documentation. The sample used was one Class X as an experimental class for large-scale trials with 15 students. Data were analyzed qualitatively and qualitatively. The results of this study indicate that: (1) The feasibility of android-based learning media can be seen from the average assessment of the Material validation test of 98.65%, Media validation test of 92.5%, Construct validation test of 96.7%. The feasibility test of the android-based learning media is each classified with very feasible criteria. (2) The effectiveness of android learning media in improving learning outcomes is a significant difference between before and after using android learning media. Based on the results of the Wilcoxon statistical test, there is an increase in learning outcomes with an average increase (mean rank) of 7.50. While the difference in the significance of the Post Test value of student learning outcomes against the Pre Test value of student learning outcomes is 0.001 <0.05, with the conclusion that the hypothesis is accepted, namely there is a significant difference in the learning outcomes of students who use android-based learning media, and the use of android-based learning media is effective. The implications of android learning media for Arabic language learning can be seen based on the analysis of the use of class X android-based Arabic learning media, making the learning process more effective, delivering interesting material and learning methods more interactive. So that the need for interesting and interactive android-based learning media has a positive impact on Arabic language learning class X MA Al Huda Kota Kediri.